PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP PADA MATA PELAJARAN IPAS DI SDN 1 BINAKARYA BUANA - Ulfayani, Indra; Yulistia, Annisa; Profithasari, Nindy; Khairani, Fadhilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study was the low conceptual understanding in the IPAS subject among sixth-grade students at SDN 1 Binakarya Buana. This study aimed to determine the effect of the Problem Based Learning (PBL) model on students’ conceptual understanding in the IPAS subject. The research method used was a quasi-experimental research design with a nonequivalent control group design. The population of this study consisted of 45 students. The sample was determined using a non-probability sampling technique with a saturated sampling method, so the entire population was used as the research sample. Data collection techniques included test methods in the form of essay questions and non-test methods in the form of observation sheets. Hypothesis testing using simple linear regression showed that F-count was greater than F-table (25.646 > 4.35) with a significance value of 0.000 < 0.05, so it was concluded that there was a significant effect of the use of the Problem Based Learning model on students’ conceptual understanding in the IPAS subject among sixth-grade students at SDN 1 Binakarya Buana.